Purines and Adenosine Receptors in Osteoarthritis - Bruce N. Cronstein; Siddhesh R. Angle (Biomolecules, 2023)
OA is a common and debilitating condition that restricts mobility and diminishes the quality of life. Recent work indicates that the generation of adenosine at the cell surface is an important mediator of chondrocyte homeostasis, and topical application of adenosine in a slow-release form (liposomes) can halt the progression of OA and diminish the pain associated with OA. Here, we review the evidence indicating that adenosine, acting at A2A receptors, plays a critical role in endogenous and exogenous treatment and reversal of OA.